(untitled) (UNWE Yearbook, 2014)
Equal opportunities and equality among all members of society and its groups are among the values and policies of the contemporary world. A central place among these is taken by the opportunity for inclusion in the field of paid employment, the access to education and the labour market, decision-making and security. In order to reach higher employment and labour market access we usually count on the policies and action undertaken in the spheres of economy development and employment increase, on social and other types of policies, which create preconditions for improving the well-being of society and each of its members, and, therefore, reach equality on the labour market in the context of employment and professional development. The topic of the social impacts of the latest financial and economic crisis in Bulgaria is seen against the background of the country’s EU membership and the developing processes of its integration in the European economic area and, particularly, with relation to Bulgaria’s participation in implementing the common European policies and strategies and the use of the financial and other resources provided to that end.In essence, the social consequences cover a rather wide area subject of the social policy and its different directions. For the purpose of this study, we have chosen three main closely interrelated areas: employment, unemployment and the population’s income. Related to these are also some other areas that experience and cause the impacts – education, training, social security etc. Among the many aspects of employment, unemployment and labour market, more closely studied are the impacts of the so-called “vulnerable” or “disadvantaged” population groups for whom the consequences of the crisis and the policies implemented are most significant and, therefore, for whom the social exclusion, poverty and unemployment have the most significant, long-lasting and sometimes irreversible consequences.